Efektivitas Model Pembelajaran Terpadu dalam Meningkatkan Kemampuan Berpikir Kreatif dan Hasil Belajar Siswa di Sekolah - Epi Supiadi; Lilik Sulistyo; Sofia Fitri Rahmani; Rinda Riztya; Heri Gunawan (Journal on Education, 2023)
In carrying out learning, students not only need to know the content of the learning, but also need the ability to think creatively from existing learning outcomes. This research then aims to see how the integrated learning model can improve students' ability to think creatively and improve the results of student learning at school. This type of research is a qualitative research using descriptive analysis. The data used in this research comes from various research results and previous studies that still have relevance to the content of this research. The results of this study then found that the right learning media in carrying out integrated learning can improve students' ability to think creatively. In addition, the integrated learning method also causes students to understand a material as a whole, and not separately, so that in the end this can improve student learning outcomes at school.